Estudo da ação probiótica das leveduras Saccharomyces cerevisiae UFMG A-905 e Saccharomyces boulardii no tratamento da infecção induzida pelo Rotavirus em modelo experimental murino - Adriano Santos Cloves (2015)
Rotavirus is a triple layered capsid virus and double-stranded segmented genome RNA. It represents a major public health problem worldwide, leading over 500000 children under five years to death every year. Rotavirus accounts for changes in intracellular calcium levels and its multiplication causes extensive damage of the intestinal epithelium, causing a profuse watery diarrhea and, which results in electrolyte disturbance and severe dehydration. A variety of studies has investigated the benefits and the relation between the intake of probiotics and reduction of episodes and severity of Rotavirus diarrhea. Probiotics are live microorganisms which when administered in adequate amounts, provide benefits to the host. In order to evaluate the probiotic yeast Saccharomyces boulardii action and Saccharomyces cerevisiae UFMG A905 in Rotavirus infection, experiments in mice were held seeking to verify aspects such as histological alterations, production of cytokines, chemokines, and sIgA induction. The treatment with the yeast was able to prevent weight loss in animals. Both yeast samples stimulated increase in cytokine Osteopontin (OPN), which means that there is a possible relationship between OPN production and improvement of infection, which is provided by these probiotics in clinical practice. The analysis also showed that yeasts, particularly S.c. UFMG A905, induced an increase in the recruitment of mononuclear, probably monocytes/macrophages, to the site of infection, and appears to have been secondary to OPN production. The yeast S.c. UFMG A905, was also able to induce the production of sIgA, while the yeast S. boulardii had a reduced production, and show decreased efficacy in reducing the infection in this model. However, when the S. boulardii was inoculated in association with the rotavirus, it was observed that the yeast had sIgA production performance far superior than the other groups, and increased elimination of rotavirus in the feces, suggesting a physical interaction with Rotavirus. Together, these results suggest that treatment with yeast, especially S.c. UFMG A905, could have a beneficial effect against Rotavirus, via increased expression of OPN and sIgA production for preventing weight loss and increasing clearance of viral particles. The analysis also indicates a possible role of S. cerevisiae UFMG A905 as probiotics in reducing Rotavirus diarrhea.